The Mediating Role of Job Satisfaction on the Effect of Work-Family Conflict, Work Environment, Remuneration on Turnover Intention - Darma, I Putu Rai Putra; Prena, Gine Das (Yayasan Riset dan Pengembangan Intelektual, 2024)
One of the important problems in the health industry is nurse turnover intention. The aim of this research is to analyze the influence of work-family conflict, work environment, remuneration on nurses' turnover intention, mediated by job satisfaction. This research is a type of quantitative research. The research was conducted at 3 Denpasar City Private Hospitals by involving 220 female nurses as research samples. Method of collecting information using questions and answers and distributing questionnaires. Inferential analysis in this research uses a form of structural equation known as Partial Least Square (PLS). Research results prove that work-family conflict has a positive and important influence on turnover intention. Work-family conflict has a negative and important influence on job satisfaction. Job satisfaction has a negative and important influence on turnover intention. Work environment has a positive and important influence on turnover intention. Remuneration has a negative and important influence on turnover intention. Remuneration has a positive and important influence on job satisfaction. The research results provide implications for resource conservation theory and role theory explaining that work-family conflict arises due to pressure on the resources available to individuals, giving rise to role conflict between work and family.